Fabrication and application of graphene-based silicone grease - Phuong Thi Mai; Nghia Phan Trong Nguyen; Tuyen Viet Nguyen; Phan Ngoc Minh; Thu Ha Thi Vu; Hang Thi Au; Thang Hung Bui (Materials Research Express, 2023)
With the increasing power requirements of integrated circuits, the demand for efficient cooling has followed suit. Silicone grease is commonly used due to its thermal stability and ability to fill in airgaps between the electronic components and radiators. Previous works attempted to increase the grease’s thermal conductivity by adding various additives such as boron nitride or functionalized carbon nanotubes. Functionalized graphene was chosen in this study due to its exceptional physical and chemical properties. Results show that the functionalization with several acid mixtures combined with ball milling resulted in a compound chemically equivalent to graphene and thoroughly dispersed in silicone grease. An optimal grease was produced, containing 1 wt% Gr-COOH and possessing a thermal conductivity of 6.534 W mK ^−1 . The resulting grease’s performance in thermal dissipation and approximated lifespan improvements was compared to a commercially available silicone grease using a 200 W LED. Results indicated a 4.5 °C decrease in saturation temperature of LED chip along with a 257% increase in thermal conductivity.